Liolaemus lizards (Squamata: Liolaemidae) as hosts for the nymph of Amblyomma parvitarsum (Acari: Ixodidae), with notes on Rickettsia infection - Muñoz-Leal, Sebastian (2016)
Adults of Amblyomma parvitarsum are common ectoparasites of South American camelids of the genera Lama and Vicugna, occuring in highlands of Argentina, Bolivia, Chile, Peru and also in Argentinean Patagonia. Whereas larval stages of this tick are known to feed on small lizards, host records for the nymphal instar have remained unreported. Supported by morphological and molecular analyses, herein we report A. parvitarsum nymphs parasitizing two Liolaemus species (Reptilia: Squamata) in the Andean Plateau of Argentina and Chile. Additionally, by a PCR screening targetting gltA and ompA genes, DNA of Rickettsia was detected in one of the collected nymphs. Obtained sequences of this agent were identical to a recent Rickettsia sp. described infecting adults of this tick species in Chile and Argentina.